2018
DOI: 10.1089/crispr.2017.0009
|View full text |Cite
|
Sign up to set email alerts
|

Allele-Specific CRISPR-Cas9 Genome Editing of the Single-Base P23H Mutation for Rhodopsin-Associated Dominant Retinitis Pigmentosa

Abstract: Treatment strategies for dominantly inherited disorders typically involve silencing or ablating the pathogenic allele. CRISPR-Cas nucleases have shown promise in allele-specific knockout approaches when the dominant allele creates unique protospacer adjacent motifs that can lead to allele-restricted targeting. Here, we present a spacer-mediated allele-specific knockout approach that utilizes both SpCas9 variants and truncated single-guide RNAs to achieve efficient discrimination of a single-nucleotide mutation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
59
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(60 citation statements)
references
References 46 publications
1
59
0
Order By: Relevance
“…While alleles can be effectively distinguished via CRISPR approaches in cases where a unique PAM is present in one allele [19,20], discrimination between alleles with single nucleotide mismatches within the sgRNA site is conceptually challenging given the promiscuity of sgRNA recognition [16,17,18]. In this regard, previous studies have shown promise in utilizing SNPs in the sgRNA target regions to achieve allele-specific mutagenesis [21,22,23,24,25]. Our results now extend allele-specific applications to HR-mediated gene targeting.…”
Section: Allele-specific Editing Of the Brca2 Locusmentioning
confidence: 76%
See 1 more Smart Citation
“…While alleles can be effectively distinguished via CRISPR approaches in cases where a unique PAM is present in one allele [19,20], discrimination between alleles with single nucleotide mismatches within the sgRNA site is conceptually challenging given the promiscuity of sgRNA recognition [16,17,18]. In this regard, previous studies have shown promise in utilizing SNPs in the sgRNA target regions to achieve allele-specific mutagenesis [21,22,23,24,25]. Our results now extend allele-specific applications to HR-mediated gene targeting.…”
Section: Allele-specific Editing Of the Brca2 Locusmentioning
confidence: 76%
“…Our results now extend allele-specific applications to HR-mediated gene targeting. Notably, allele selectivity can be further improved with a truncated sgRNA design [25], since it displays an even lower tolerance to mismatches [26]. These efforts have substantially broadened the scope of allele-specific applications to achieve various desired outcomes.…”
Section: Allele-specific Editing Of the Brca2 Locusmentioning
confidence: 99%
“…The reaction was stopped by adding 2.5 μL of 200 mM EDTA. Indel frequencies were estimated as previously described71 by calculating band intensities with ImageJ software (NIH) and applying the following equation: % indels=100×[1−(1−fcut) 1/2 ], where fcut is the fraction cleaved, corresponding to the sum of intensities of the cleaved bands divided by the sum of total band intensities.…”
mentioning
confidence: 99%
“…3 CRISPR-Cas9-mediated allele knock-out based on error-prone non-homologous end joining (NHEJ) can correct gain-of-function mutations with AAV. 47 However, many loss-of-function mutations in larger genes still require local replacement with a wildtype sequence (scarless genome editing).…”
mentioning
confidence: 99%